Numerical analysis on deformation behavior of High Entropy Alloy (HEA) under compression test - Nordin, Norhuda Hidayah; Mohamad, Faiz Syazwan; lsmail, Izham lzzat; Sulaiman, Mohd Hafis (Springer Nature Singapore PteLtd.2022, 2022)
The mechanical properties of a material reflect the relationship between its response to or deformation from an applied load or force. It determines the range of usefulness of a material and establishes the service life that can be expected. The importance of mechanical properties includes strength, hardness, ductility and stiffness. These properties are ascertained by performing carelully designed laboratory experiments that replicate as closely as possible the service conditions. The introduction to novel high entropy alloys (HEAs) which consists of multicomponent elements have been attracting considerable attention all over the world, particularly in the recent years. HEAs reported to exhibit exceptional mechanical properties at various conditions of surrounding and expected to be applied in engineering application. This paper discusses the mechanical properties of FeCoNiAIBSi HEA under compression condition with increasing of boron content. The deformation behaviour during this condition of the FIEA was analysed numericaily by using LS-Dyna software. The piecewise linear plasticity material model was used to investigate the deformation of the HEA. An inverse finite element method was introduced to determine the optimum friction properties of each model. Increasing of friction coefficient was proven to increase the strength of the material. The validation on the numerical analysis was done by comparing the simulated stress-strain curve and geometry with the experimental value for each HEA sample. The deformation behavior was discussed through the morphology analysis of the samples. It was found that increase in boron content changed the structure of the FIEA and thus altered its mechanical properties.